2017
DOI: 10.1111/liv.13392
|View full text |Cite
|
Sign up to set email alerts
|

Management and prognosis of hepatocellular carcinoma in the elderly: Results of an in‐field multicenter cohort study

Abstract: Age per se does not impact on short-mid-term prognosis (≤24 months) of HCC patients, and should not represent a limitation to its management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
(91 reference statements)
4
14
0
Order By: Relevance
“…ECOG score and tumor stages should be the most important factors considered rather than age for treatment selection in elderly patients. These findings were consistent with some other studies that surgical resection and some non-surgical treatments attained the equivalent long-term survival in older with younger patients [ 10 , 14 , 15 , 21 , 22 ] ( Table 5 ). Therefore, older patients can have comparable long-term outcome to younger patients when appropriately selected and treated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…ECOG score and tumor stages should be the most important factors considered rather than age for treatment selection in elderly patients. These findings were consistent with some other studies that surgical resection and some non-surgical treatments attained the equivalent long-term survival in older with younger patients [ 10 , 14 , 15 , 21 , 22 ] ( Table 5 ). Therefore, older patients can have comparable long-term outcome to younger patients when appropriately selected and treated.…”
Section: Discussionsupporting
confidence: 93%
“…However, the proportion of HCC within BCLC stages 0-A, B and C were similar distributed between older and younger patients. Consistently, some studies found similar tumor stages between older and younger patients with HCC [ 10 , 14 , 15 , 25 ], but others reported earlier tumor stages in elderly patients [ 16 , 21 , 26 ] ( Table 5 ). Thus, the discrepancy of tumor stages between older and younger patients must reflect the difference of patient inclusion and treatment indication of elderly patients in different institutions.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…This finding may be explained that HBV is transmitted vertically in the perinatal period, whereas HCV is more infected at a later stage in life, and therefore, patients with HBV-related HCC tended to be significantly younger than patients with HCV-related HCC. 10 Our data showed that chronic viral hepatitis was the major risk factor contributing to the development of HCC and majority were males. This study revealed that HCC was more prevalent in males, which is in agreement with previous studies, 16,17 as well as other local and regional studies.…”
Section: Discussionmentioning
confidence: 58%
“…It was found that HBV‐related HCC was mostly found in 41‐60 years old, while HCV‐related HCC was mostly in ≥61 years old. This finding may be explained that HBV is transmitted vertically in the perinatal period, whereas HCV is more infected at a later stage in life, and therefore, patients with HBV‐related HCC tended to be significantly younger than patients with HCV‐related HCC …”
Section: Discussionmentioning
confidence: 98%